VIABILITAS DAN PERTUMBUHAN BENIH SEMANGKA NON BIJI (Citrullus vulgaris Schard) TERHADAP PENGARUH SUHU DAN PEMECAHAN KULIT LUAR - Tutik Nugrahini (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2015)
The purpose of this research is to determine the effect of temperature and outer rind peeling and their interactions on the viability and growth of seedless watermelon seedlings, and  to obtain the appropriate temperature and the outer rind peeling for resulting good seed of seedless watermelon.Research conducted at the Laboratory of the Faculty of Agriculture, University of Widya Gama Samarinda Mahakam from March to June 2014.  It applied 2 x 4 factorial experiment in a completely randomized design and repeated 6 times.  The first factor is the treatment of temperature (T) with 4 levels, namely: the temperature of 28-300C (t1), a temperature of 30-320C (t2), a temperature of 32-340C (t3), and a temperature of 34-360C.  The second factor is the outer rind peeling (P) with 2 levels, namely: no rind peeling (p0) and with the outer rind peeling (p1).Observational data collected in the study, namely: (1) age when the seeds begin to germinate, (2) the germination of seeds, (3) the length of radicle, (4) age in leaf formation, and (5) the number of leaves. Data analysis was performed using analysis of variance and when significant (F count> F table 5%) or highly significant (F count> F table 1%), then further tested by Duncan's multiple range test (DMRT) level of 5% .The results showed that: (1) the effect of the interaction between the outer rind peeling and different temperatures factors affected very significantly on to the age of the seeds begin to germinate, seed germination, radicle length, age of  the leaf formation, and number of leaves;  and (2) the combination treatment with outer rind peeling and a temperature of 30 - 32oC (p1t2) produces the best viability and growth of seedless watermelon.